Integrating bioinformatics and experimental validation to Investigate IRF1 as a novel biomarker for nucleus pulposus cells necroptosis in intervertebral disc degeneration - Kaisheng Zhou; Shaobo Wu; Zuolong Wu; Rui Ran; Wei Song; Hao Dong; Haihong Zhang (Scientific Reports)
Abstract Intervertebral disc degeneration (IDD) is a prevalent spinal disorder and the principal cause of lower back pain (LBP). Diverse forms of programmed cell death (PCD) have been identified as the key phenotypes of the disease and have the potential to serve as new indicators for the diagnosis and prognosis of IDD. However, the mechanism underlying necroptosis in IDD remains unclear. This study aimed to identify novel biomarkers that promote nucleus pulposus cell necroptosis in IDD using bioinformatic analysis and experimental validation. We analyzed multiple datasets of IDD from the Gene Expression Omnibus (GEO) database to identify necroptosis-related IDD differential genes (NRDEGs). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed, followed by logistic least absolute shrinkage and selection operator (LASSO) and support vector machine-recursive (SVM) algorithms to identify key genes. Gene set enrichment analysis (GSEA) and logistic regression analysis were used to ascertain the potential functions of these genes and to identify key genes, respectively. We then constructed mRNA-miRNA, mRNA-TF, mRNA-drug, and functional similarity gene interaction networks for the seven key genes identified. We used IDD clinical samples and necroptotic cell model to validate our findings. Immunohistochemical staining, RT-qPCR, and western blotting results indicated that IRF1 may be a hub necroptosis-related gene. To further elucidate the function of IRF1, we constructed IRF1 knockdown and overexpression models, which revealed that IRF1 promotes necroptosis in rat nucleus pulposus cells, increases mitochondrial ROS levels, and decreases ATP levels. These findings provide new insights into the development of necroptosis in IDD and, for the first time, validate the role of IRF1 as a novel biomarker for the diagnosis and treatment of IDD.